2013
DOI: 10.3168/jds.2013-6682
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactoglobulin-linoleate complexes: In vitro digestion and the role of protein in fatty acid uptake

Abstract: The dairy protein β-lactoglobulin (BLG) is known to bind fatty acids such as the salt of the essential longchain fatty acid linoleic acid (cis,cis-9,12-octadecadienoic acid, n-6, 18:2). The aim of the current study was to investigate how bovine BLG-linoleate complexes, of various stoichiometry, affect the enzymatic digestion of BLG and the intracellular transport of linoleate into enterocyte-like monolayers. Duodenal and gastric digestions of the complexes indicated that BLG was hydrolyzed more rapidly when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…However, using a Caco-2 monolayer that mimics the intestinal barrier in combination with confocal imaging, the transport of linoleate into Caco-2 cells was decreased in the presence of β-lg in agreement with the cytotoxicity study (Le Maux et al 2013b). Retinol and palmitic acid were also transported more efficiently across the monolayer in its free form than in complex with β-lg (Puyol et al 1995; Riihimäki-Lampén 2009).…”
Section: Biological Properties Of the β-Lactoglobulin/ligand Complexessupporting
confidence: 85%
“…However, using a Caco-2 monolayer that mimics the intestinal barrier in combination with confocal imaging, the transport of linoleate into Caco-2 cells was decreased in the presence of β-lg in agreement with the cytotoxicity study (Le Maux et al 2013b). Retinol and palmitic acid were also transported more efficiently across the monolayer in its free form than in complex with β-lg (Puyol et al 1995; Riihimäki-Lampén 2009).…”
Section: Biological Properties Of the β-Lactoglobulin/ligand Complexessupporting
confidence: 85%
“…However, the dissociation is reversible so that the reformation of the complex upon increase in the pH value can occur. 153 Furthermore, it has been postulated that small hydrophobic molecules inside the calyx may be protected from the environment by a closed EF-loop. 150 Thus, complexation is affected by the size and chemical structure of the BC.…”
Section: Protein Based Enmmentioning
confidence: 99%
“…157 Despite the high pH value in the intestinal lumen, a release of substances located in the calyx can occur near cell surfaces where a lower pH is present and therefore dissociation of the complex is favoured. 153 Caseins have a large number of proline residues, a high net charge and low intrinsic hydrophobicity leading to a unique unfolded structure under native conditions. In milk, caseins are usually present in the form of micelles which are formed by hydrophobic interactions and colloidal calcium phosphate bridges and are 50-500 nm in diameter.…”
Section: Protein Based Enmmentioning
confidence: 99%
“…Moreover, they demonstrated that 12 % of riboflavin recommended daily dose reached the intestine if 100 mL of a food simulant solution was ingested. Le Maux, Brodkorb, Croguennec, and Hennessy (2013) investigated the potential changes in β-Lg/linoleate complex after static in vitro digestion, as well as the linoleate acid bioaccessibility and their intracellular transport into Caco-2 cells. These authors demonstrated that binding β-Lg to linoleic acid influences the protein susceptibility to digestion.…”
Section: Introductionmentioning
confidence: 99%